2008
DOI: 10.1086/591944
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Intermittent Preventive Treatment with Sulfadoxine‐Pyrimethamine, Amodiaquine, or the Combination in Pregnant Women in Ghana

Abstract: Clinicaltrials.gov identifier: NCT00146783 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 38 publications
0
49
0
Order By: Relevance
“…These findings may partially explain why IPTp-SP has demonstrated noninferiority against more potent antimalarial compounds in several randomized clinical trials of IPTp, particularly in studies measuring LBW and preterm birth as endpoints [20–24]. Sulfadoxine is a broad-spectrum antibiotic that likely exerts an inhibitory effect against nonmalaria causes of LBW and preterm birth [25].…”
Section: Discussionmentioning
confidence: 99%
“…These findings may partially explain why IPTp-SP has demonstrated noninferiority against more potent antimalarial compounds in several randomized clinical trials of IPTp, particularly in studies measuring LBW and preterm birth as endpoints [20–24]. Sulfadoxine is a broad-spectrum antibiotic that likely exerts an inhibitory effect against nonmalaria causes of LBW and preterm birth [25].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of IPTp-SP efficacy have been done in areas with either minimal or very high prevalences of the quintuple mutant [15,25,28,29]. For example in Ghana where triple, but no quintuple mutations have been found, an in vivo study confirmed good efficacy of IPTp-SP [30,31]. In Benin where prevalence of the quintuple mutation was less than 10% prior to ITPp-SP treatment, one study found 11% of patients had parasitological failure at 1 month of follow up [32].…”
Section: Discussionmentioning
confidence: 99%
“…Where adverse events due to SP have been assessed in trials these have been seen in a high proportion of women 48% and 41% in Ghana [21], [22]. The side effects have included general body weakness, dizziness, vomiting, nausea, abdominal pain, diarrhoea, body itch, and body rash.…”
Section: Discussionmentioning
confidence: 99%